2018
DOI: 10.1016/j.ajog.2018.06.012
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in the burnout profile of chairs of academic departments of obstetrics and gynecology over the past 15 years

Abstract: Chairs of academic departments of obstetrics and gynecology continue to face significant job-related stress. Burnout has decreased; however, personal accomplishment scores have also declined most likely due to administrative factors that are beyond the chairs' perceived control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Chairpersons typically maintain heavy workloads as they are challenged with balancing a variety of faculty and administrative priorities, which could include patient care. 4,5 Based on the limited literature in medicine, [1][2][3] our results in pharmacy schools show similarities to chairs in medical programs as many have a clinical background as well as relatable shared experiences with their faculty. This is the first study to determine the proportion and determinants of clinical pharmacy chairpersons that maintain an active clinical practice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Chairpersons typically maintain heavy workloads as they are challenged with balancing a variety of faculty and administrative priorities, which could include patient care. 4,5 Based on the limited literature in medicine, [1][2][3] our results in pharmacy schools show similarities to chairs in medical programs as many have a clinical background as well as relatable shared experiences with their faculty. This is the first study to determine the proportion and determinants of clinical pharmacy chairpersons that maintain an active clinical practice.…”
Section: Discussionmentioning
confidence: 80%
“…In medical schools, it is very common for physician department chairpersons to maintain some clinical patient care practice. 1,2 Participation in practice by medical school department chairpersons is influential as it provides shared perspective, modeling, and a foundation for practice policy development for medical faculty. 3 having a practice prior to becoming chair (P = .001), having a higher clinical service expectation (P < .0001), and having a lower administrative percentage (P = .0003).…”
Section: Introductionmentioning
confidence: 99%
“…This rapid review identified 79 studies reporting on current prevalence estimates of burnout among U.S. health care providers (Adler et al, 2017;Agrawal et al, 2020;Ahmed et al, 2020;Anandarajah, Quill, and Privitera, 2018;Attenello et al, 2018;Ayyala et al, 2019a;Beck et al, 2020;Blechter et al, 2018;Britt, Koranne, and Rockwood, 2017;Bundy et al, 2020;Cheng et al, 2020;Chew et al, 2017;Creager, Coutinho, and Peterson, 2019;Cull et al, 2019;Del Carmen et al, 2019;Domaney, Torous, and Greenberg, 2018;Doolittle, 2020;Dyrbye et al, 2018;Dyrbye et al, 2020;Edwards, Helfrich, et al, 2018;Fargen et al, 2019;Gabbe et al, 2018;Garcia et al, 2018;Garcia et al, 2020;Gardner et al, 2019;Goldberg et al, 2020;Gribben, Kase, et al, 2019;Gribben, MacLean, et al, 2019;Guenette and Smith, 2017;Hansen et al, 2018;Harris et al, 2018;Hauer, Waukau, and Welch, 2018;Hu et al, 2019;Hughes, Francis, and Sciscione, 2019;Jackson et al, 2017;Kamal et al, 2016;Kemper et al, 2020;Knox et al, 2018;Kroll et al, 2020;Kroth et al, 2019;…”
Section: Relationships Among the Publicationsmentioning
confidence: 99%
“…There is also some evidence suggesting that fewer physicians in academia experienced burnout than did physicians without an academic position (Gabbe et al, 2018;Porter et al, 2018;Summers et al, 2019).…”
Section: Physiciansmentioning
confidence: 99%
“…According to the Brand and Holsboer-Trachsler model [4], burnout is the result of a combination of personality traits (such as perfectionism, overidentification with job, high sense of duty combined with low social integration and peer adjustment) and workplace-related conditions (high demand and low control, poor support from colleagues and managers). At the same time, other models consider other personality traits as burnout factors -e.g., self-efficacy [5], extraversion, conscientiousness, openness [6], coping strategies, mindfulness [7], and conditions associated with the workplace (the average number of hours of sleep per night and number of working hours per week [8]). There is a consensus that burnout may also be based on various stress-related neuroendocrine mechanisms [9,10].…”
Section: Introductionmentioning
confidence: 99%